Genetic testing and prognosis of sarcomatoid hepatocellular carcinoma patients - Jia, Bin; Xia, Peiyi; Dong, Junqiang; Feng, Wenhao; Wang, Wenjia; Liu, Enjie; Jiang, Guozhong; Qin, Yanru (Frontiers in Oncology, 2023)
Background：Primary hepatic sarcomatoid carcinoma (HSC) is a rare epithelial malignancy with high invasiveness and poor prognosis. However, the molecular characteristics and main driver genes for HSC have not been determined. The aim of this study is to explore the potential actionable mutations of driver genes, which may provide more therapeutic options for HSC. 2.Methods：In this study, DNA extraction and library preparation were performed using tumor tissues from 28 HSC patients. Then we used Miseq platform (Illumina) to sequence the target-enriched library , and we aligned and processed the sequencing data. The gene groups were tested for SNVs/Indels/CNVs. Tumor mutation burden (TMB) was assessed by the 425-cancer relevant gene panel. Multivariate analysis of COX’s model was used for survival analysis (OS) of patients' clinical characteristics. 3.Result：All patients died of cancer by the end. The median overall survival (OS) of the patients was only 4 months. TP53, TERT and KRAS were the top three frequently mutated genes, with frequencies of 89.3%, 64.3% and 21.4%, respectively. A considerable number of patients carried mutations in genes involving in the TP53 pathway (96%) and DDR pathway (28%). Multiple potentially actionable mutations, such as MET fusions, NTRK1 fusions and BRCA1/2 mutations, were identified in HSCs. 4.Conclusions: This study shows a landscape of gene mutations in HSC. HSC has high mutation rates in TP53 pathway and DDR pathway. The potential actionable mutations of driver genes may provide more therapeutic options for HSC.